Reduction in adhesive shear strains at the ends of bonded reinforcements - Tran-Cong, Thanh (Research report (Defence Science and Technology Organisation (Australia)) ;, 1997)
A mathematical model is presented which defines the adhesive shear strain distribution for an adherend with bonded multilayer reinforcements which are stepped at their ends. In this one-dimensional formulation each step is allowed to be of different thickness and modulus, and of variable step length. A procedure is then given to improve the design of such reinforcements through minimising the peak adhesive shear strain which typically occurs near their stepped ends. It is shown that to achieve a 20% reducation in peak adhesive shear strain for a typical stepped patch consisting of unidirectional laminae, the first step adjacent to the patch end needs to be much longer that the remaining steps. For the case where cross-ply laminae are used in conjunction with unidirectional laminae, the maximum shear strain in the adhesive layer can be reduced by about 60%